(3GdOdGFd aj TQM eG CZadg CHh YHjO hGHf bJjHI ef ZQjH GdMOjKs - (3CHh eMeO bGSe Hf KGHJ GdSQbSWis; (3CHh GdaVd eMeO Hf GdbGSe GdYLdGfjs
(3ChdgG (B:s
(3hbGd ai MOjK GdfHi Udi Gddg Ydjg hSde Cfg CJi HUdGdI TGg hCcd efgG Ke Udi hde jJhVC s
(3BNQgG (B:s
(3ai bhd GHf eSYhO cQGgjI Cf jYde KdGK dZGJ cQGgjI hcQGgI hcQGgjf bGd CHh RjO SeYJ EYQGHjkG ef Hfi Jeje jbhd CJjJc cQGgjf Cf JZVH s
(3Jhai GdeDda bHd EJeGeg hCcedg CHhg GdPi Jhai SfI (B313 (3g` bGd CHh Ydi GdbGdi Yfg Efg de jDda eKdg ai GdeZQH hbGd GHf GdaQV hdG ai GdeTQb s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs